Stigmas of the reality stage. Issue 1 (1st August 2022) - Weidman, Amanda
This article focuses on the symbolic work around gender accomplished by singing reality shows in South India. Examining moments from Tamil-, Malayalam- and Telugu-language reality shows aired in the 2010s, and using ethnographic research conducted during the shooting of episodes of one of these popular reality shows, Airtel Super Singer Junior, in Chennai from the early 2010s, it shows how, through the reality shows' staging and contest format, contestants are subjected to different and often conflicting regimes of evaluation. While the shows' emphasis on performance and visual presentation and consumption is certainly a factor in the way the shows manage these conflicting pressures, equally as important are the different ways that talk about and around the performance functions, both to increase the cultural capital of singing film songs and to create entertainment value, producing unscripted, seemingly 'spontaneous' moments that catch the contestants and judges off guard. Talk functions to reduce stigma in some places while amplifying it in others. While elevating the cultural capital of a formerly 'lowbrow' domain, these shows simultaneously place the singer in an increasingly precarious position, producing distinctly gendered stigmatizing effects for both the female contestants and the playback singers who serve as judges.